2006
DOI: 10.1021/es052508d
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reductive Debromination of Polybrominated Diphenyl Ethers (PBDEs)

Abstract: Polybrominated diphenyl ethers (PBDEs) are a class of widely used flame retardants that have recently been detected in environmental samples, diverse biota, human blood serum, and breast milk at exponentially increasing concentrations. Currently, little is known about the fate of these compounds, and in particular, about the microbial potential to degrade them. In this study, debromination of deca-BDE and an octa-BDE mixture is demonstrated with anaerobic bacteria including Sulfurospirillum multivorans and Deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
210
4
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(226 citation statements)
references
References 34 publications
8
210
4
4
Order By: Relevance
“…[32][33][34] In this study, the BDE 209 concentration was two orders of magnitude higher than other congeners. Thus the contribution of lower brominated congeners from BDE 209 degradation may not be negligible.…”
Section: Congener Patterns and Possible Sourcesmentioning
confidence: 51%
“…[32][33][34] In this study, the BDE 209 concentration was two orders of magnitude higher than other congeners. Thus the contribution of lower brominated congeners from BDE 209 degradation may not be negligible.…”
Section: Congener Patterns and Possible Sourcesmentioning
confidence: 51%
“…Previous studies have reported on the photodegradation of BDE-209 to less brominated PBDE congeners in various solid matrices such as sediment, sand, and soil [34,35]. Microbial reductive debromination of BDE-209 and octa-BDEs mixtures under pure culture conditions has also been reported [36,37]. Furthermore, a recent study showed that BDE-209 may be degraded by microorganisms in anaerobic sediment to lessbrominated congeners, such as BDE-99, -47, and -66, and that BDE-99/-47 can also be transformed to BDE-28, BDE-17 by reductive debromination [38].…”
Section: Principal Component Analysis Of Pbde Congener Profilesmentioning
confidence: 93%
“…S1 in the Supplemental material), which were similar to the profiles of the common technical penta-BDE mixtures . First, the contributions from BDE183 in the current sediments were significantly elevated compared with those collected in 2002 (p b 0.001), except for the Xijiang River and the PRE for two possible reasons: i) the release of PBDEs derived from the penta-BDE mixture decreased by a greater degree than BDE183 (a main ingredient of the octa-BDE mixture) after their regulation in 2006 in China, and/or ii) more BDE183 was generated from the microbial or photolytic debromination of highly brominated BDEs relative to other BDE congeners (Bezares-Cruz et al, 2004;He et al, 2006). Second, there was an apparent change (although not statistically significant for all cases) in the ratio of BDE47/(BDE47+ BDE99) between the current and previous (Fig.…”
Section: Composition Profiles and Implications For Environmental Procmentioning
confidence: 99%